2015
DOI: 10.1007/s00464-015-4140-y
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted laparoscopic versus open pancreaticoduodenectomy: a prospective, matched, mid-term follow-up study

Abstract: This first largest, prospective matched study demonstrated that for treating selected borderline and malignant pathologies, RLPD was associated with a significant learning curve effect and expedited postoperative recovery, but had a surgical and oncological safety profile similar to OPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
154
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 159 publications
(168 citation statements)
references
References 38 publications
11
154
0
3
Order By: Relevance
“…A reduction of 16 days in the median length of hospital stay after RAPD was reported when a surgeon moved from Italy to the US [8]. Interestingly, Chen et al [14] reported a mean length of stay exceeding 20 days, in agreement with our results.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…A reduction of 16 days in the median length of hospital stay after RAPD was reported when a surgeon moved from Italy to the US [8]. Interestingly, Chen et al [14] reported a mean length of stay exceeding 20 days, in agreement with our results.…”
Section: Discussionsupporting
confidence: 83%
“…The learning curve (LC) of RAPD was recently reported by 2 independent groups, both describing the concurrent LC of 2 surgeons [13,14]. We herein provide the first description of the LC of a single surgeon in RAPD.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations